1991
DOI: 10.1111/j.1365-2826.1991.tb00296.x
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Vasopressin in the Stress‐Induced Inhibition of Gonadotrophin Secretion: Studies in the Brattleboro Rat

Abstract: The effects of stress on the secretion of adrenocorticotrophin, corticosterone and luteinizing hormone (LH) in rats congenitally lacking hypothalamic vasopressin (Brattleboro rats) and in normal controls of the parent strain (Long Evans) have been compared in an attempt to examine the role of vasopressin in the stress-induced depression of gonadotrophin secretion. In the Long Evans rats, stress (0.6 mg/100 g histamine, ip) initiated, within 5 and 20 min respectively, significant (P< 0.01, Student's t-test) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
4
5
0
Order By: Relevance
“…Basal A C T H and p -E N D levels were the same in DI and L E rats. For A C T H this is in agreement with some studies [24,26] while other studies have shown lower basal A C T H levels in D I rats when compared to LE rats [27][28][29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Basal A C T H and p -E N D levels were the same in DI and L E rats. For A C T H this is in agreement with some studies [24,26] while other studies have shown lower basal A C T H levels in D I rats when compared to LE rats [27][28][29].…”
Section: Discussionsupporting
confidence: 92%
“…For A C T H , this finding is in agreement with previous studies where the A C T H response to other stressors was found to be smaller in D I than in LE rats [28,29]. Furthermore, some earlier studies showed an im paired corticosterone response to stress [30][31][32][33], but these results do not necessarily reflect the A C T H secre tion since the adrenal response to A C T H may be lower in D I rats [33].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, both the polyclonal antibody employed in the present study and the N-terminal lipocortin fragment (LCI have been shown to modulate thermogenesis (65) and ischaemic damage (66, 67) when given centrally. Since histamine elicits the release of both CRF-41 and AVP from the hypothalamus (64) it is also possible, in view of our in vitro findings, that any inhibitory effect of LCI on CRF-41 secretion was masked by a concomitant rise in AVP release. Indeed, an increase in AVP release may explain the potentiation of the adrenocortical response to histamine observed in vivo with the lowest dose of LCI.…”
Section: Discussionmentioning
confidence: 86%
“…Arginine vasopressin (AVP) has been reported to mediate suppressive effects of stress on LH secretion ( 16), and to play a role in compensation for the CRH deficiency ( 17). In addition, AVP and CRH synergistically stimulate corticotropin release from the isolated perfused anterior pituitary cells ( 18).…”
Section: Discussionmentioning
confidence: 99%